Evaluation Model for Vertical Handoff Algorithms (2012)
This chapter begins by introducing the problem of vertical handoff in heterogeneous wireless networks and illustrates the lack of a proper evaluation model to compare the different Vertical Handoff Algorithms (VHAs) that have been proposed in the literature over the last few years. In the following sections, a novel evaluation model for VHAs is introduced and described. The design of the new evaluation model is based on the multi-criteria evaluation methodology and criticality analysis, which permitted the model to be developed as a software component. The new proposed evaluation model is flexible in terms of the number of evaluation parameters and facilitates the analysis of VHAs by researchers. A specific case study considering some VHAs is presented, analyzed, and discussed in detail. The case study is used to compare the proposed evaluation model with another evaluation model (Ordinal Model) for VHAs.